Generalized multiprotocol label switching an overview of routingand management enhancements. - Banerjee, A.
Generalized multiprotocol label switching, also referred to as multiprotocol lambda switching, supports not only devices that perform packet switching, but also those that perform switching in the time, wavelength, and space domains. The development of GMPLS requires modifications to current signaling and routing protocols. It has also triggered the development of new protocols such as the Link Management protocol. We present the traffic engineering enhancements to the Open Shortest Path First Internet routing protocol and ISIS Intradomain Routing Protocol, two popular routing protocols, to support GMPLS. We present the concepts of generalized interfaces, label-switched path hierarchy, and link bundling intended to improve GMPLS scalability. We also discuss the Link Management Protocol which can be used to make the underlying links more manageable
Keywords: ATM; DWDM; GMPLS; GMPLS scalability; IP address assignment; ISIS Intradomain Routing Protocol; Internet routing protocol; Open Shortest Path First protocol; SONET/SDH.; TDM; Generalized interfaces; Generalized multiprotocol label switching; Label-switched path hierarchy; Link bundling; Link management protocol; Multiprotocol lambda switching; Packet switching; Routing protocols; Signaling protocols; Space domain switching; Synchronous digital hierarchy; Synchronous optical network; Time domain switching; Time-division multiplexing; Traffic engineering enhancements; Wavelength domain switching